A Dietary Assessment Training Course Path: The Italian IV SCAI Study on Children Food Consumption - Turrini, Aida; Catasta, Giovina; Censi, Laura; Comendador Azcarraga, Francisco Javier; D'Addezio, Laura; Ferrari, Marika; Le Donne, Cinzia; Martone, Deborah; Mistura, Lorenza; Pettinelli, Antonella; Piccinelli, Raffaela; Saba, Anna; et al. (Frontiers in Public Health, 2021)
The food model of population can be estimated through dietary surveys in which open-ended food section forms such as diaries and interviews, or semi-quantitative food frequency questionnaires are administered. A harmonized dietary survey methodology together with a standardized operational procedure in conducting the study are crucial to ensure accuracy of information and comparability, so reducing uncertainty and increasing reliability of the results. Dietary patterns i) include several target variables (foods, nutrients, other substances), ii) require several explanatory variables (age, sex, anthropometric measurements, socio-economic characteristics, life-style, preferences related to culture, organization of food-related activities, etc.), and iii) have impacts in several domains: imbalance diets, acute (e.g., microbiological risk) and chronic (non-communicable diseases) exposure affect health and then sanitary expenditure. To the other hand, food demand has impacts on food system: production, distribution and food services system; food wastes and other wastes generated by food-related activities of the households (e.g., packaging disposal) have consequences on “health of the planet” that in its turn can again have effects on human health. Harmonization and standardization in such complexity require an ad hoc structured information system made by databases (food nomenclatures, portion sizes, food atlas, recipes) and methodological tools (quantification methods, food coding systems, assessment nutritional status, data processing to extrapolate what we consider validated dietary data). The hypothesis of the present work, is that a specialized professional community in dietary data management will allow for building a permanent surveillance system in the short term and may reduce costs, to arrange a training re-training system to maintain the specialization and to prepare the turnover within the community. A training system in this field also requires updating the knowledge of technological tools for collecting food consumption data currently under development, especially, but not limited to, web-based and smartphone-based applications. Creating and maintaining the dietary data managers community is challenging but possible. CREA Food and Nutrition is here sharing the experience that can help to design supportive training system to build communities of professionals able to carry out dietary data surveillance systems generating data for health managers, food system actors, and policy makers.